2023
DOI: 10.1002/art.42380
|View full text |Cite
|
Sign up to set email alerts
|

Three Distinct Transcriptional Profiles of Monocytes Associate with Disease Activity in Scleroderma Patients

Abstract: Objective Patients with diffuse cutaneous systemic sclerosis (dcSSc) display a complex clinical phenotype. Transcriptional profiling of whole blood or tissue from patients are affected by changes in cellular composition that drive gene expression and an inability to detect minority cell populations. We undertook this study to focus on the 2 main subtypes of circulating monocytes, classical monocytes (CMs) and nonclassical monocytes (NCMs) as a biomarker of SSc disease severity. Methods SSc patients were recrui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
17
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 55 publications
(70 reference statements)
3
17
1
Order By: Relevance
“…However, when we focus on classical monocytes, our results are consistent in significance and directionality of effect to those reported by Makinde and colleagues for HPSE, CYTH4, KLF6, KYNU, C6orf62, and TUBB4B [38],…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…However, when we focus on classical monocytes, our results are consistent in significance and directionality of effect to those reported by Makinde and colleagues for HPSE, CYTH4, KLF6, KYNU, C6orf62, and TUBB4B [38],…”
Section: Discussionsupporting
confidence: 91%
“…This study has virtually no power to detect the DNA methylation differences herein reported, but is powered to detect a reasonable fraction of the differentially expressed transcripts between cases and controls. Nevertheless, with 16 total SSc cases, it is comparable to sample sizes from previous studies that assessed genome-wide DNA methylation and gene expression primarily in European Americans [16,38,90,91]. Also, our results are consistent with the heightened monocyte activation previously reported in African American patients with SSc [30,31].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations